Experimental and Numerical Analysis of Cold Formed Multi Pin Structures Using a Multi-Acting Tool Design - Römisch, David; Merklein, Marion

Versatile tool design for a tumbling self-piercing riveting process - Wituschek, Simon; Lechner, Michael

Approach to Determine the Characteristic Dimensions of Clinched Joints by Industrial X-ray Computed Tomography - Busch, Matthias; Köhler, Daniel; Hausotte, Tino; Kupfer, Robert; Troschitz, Juliane; Gude, Maik
Destructive micrograph analysis (MA) is the standard method for the assessment of clinched joints. However, during the joint preparation for the MA, geometric features of the joint can change due to elastic effects and closing cracks. X-ray computed tomography (CT) is a promising alternative to investigate the joint non-destructively. However, if the material properties of similar joining partners are the same, the CT is not able to correctly resolve surfaces in the joint that are close to or pressing onto each other. These surfaces are relevant for the determination of characteristic dimensions such as neck thickness and undercut. By placing a thin, highly radiopaque tin layer between the joining partners, the interfacial area in the reconstructed volume can be highlighted. In this work, a method for the localisation of the tin layer inside the joint as well as threshold value procedures for the outer joint contour in cross section images are investigated. The measured characteristic dimensions are compared with measured values from MA of the same samples and of samples without tin layer. In addition, possible effects of the tin layer on the joining point characteristics as well as problems of the MA are discussed.

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan Tobias; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Clinching as a mechanical joining technique allows a fast and reliable joining of metal sheets in large-scale production. An efficient design and dimensioning of clinched joints requires a holistic understanding of the material, the joining process and the resulting properties of the joint. In this paper, the process chain for clinching metal sheets is described and experimental techniques are proposed to analyze the process-microstructure-property relationships from the sheet metal to the joined structure. At the example of clinching aluminum EN AW 6014, characterization methods are applied and discussed for the following characteristics: the mechanical properties of the sheet materials, the tribological behavior in the joining system, the joining process and the resulting material structure, the load-bearing behavior of the joint, the damage and degradation as well as the service life and crack growth behavior. The compilation of the characterization methods gives an overview on the advantages and weaknesses of the methods and the multiple interactions of material, process and properties during clinching. In addition, the results of the analyses on EN AW 6014 can be applied for parameterization and validation of simulations.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Calibration of 3D scan trajectories for an industrial computed tomography setup with 6-DOF object manipulator system using a single sphere - Butzhammer, Lorenz; Müller, Andreas Michael; Hausotte, Tino (Measurement Science and Technology)
In industrial x-ray computed tomography (CT), the application of more complex scan paths in comparison to the typical circular trajectory (${360}^{°}$ rotation of the measurement object) can extend the potential of CT. One way to enable such 3D scan trajectories is to use a 6-degrees-of-freedom (DOF) object manipulator system. In our case, a hexapod is mounted on top of the rotary table of a commercial CT scanner. This allows for adaptive tilting of the measurement object during the scan. For high accuracy, the geometry calibration of such setups is typically done using the x-ray projections of a calibrated multi-sphere object. Contrary to this, here, we demonstrate a procedure that is based on only a single sphere and can therefore experimentally be implemented with low effort. Using the intrinsic geometry parameters of the CT device as prior information, the hexapod coordinate system with respect to the CT machine coordinate system is determined by means of a one-step optimization approach. The resulting parameters are used to calculate projection matrices that enable the volume reconstruction for 3D scan trajectories. The method is validated using simulated x-ray images and experimental investigations including dimensional measurements. For the used setup, geometric measurement results for 3D scan trajectories that are calibrated with the presented method show in sum increased errors compared to the circular scans. A limited pose accuracy of the manipulator system is discussed as a potential cause. The results nevertheless indicate that the presented method is generally feasible for dimensional CT measurements provided that the pose accuracy is sufficient. The calibration procedure can therefore be a low-cost and easier to implement alternative compared to trajectory calibration methods based on multi-sphere objects, but with a tendency towards lower measurement accuracy. The methodology can in principle be transferred to different setups with 6-DOF manipulator systems, e.g. C-arm CT devices with a robot arm.
Keywords: Applied Mathematics; Instrumentation; Engineering (miscellaneous)

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, Werner; Martins, P.A.F.; Bobbert, Mathias; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fiber reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processes.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Geometric and mechanical joint characterization of conventionally and tumbled self-piercing riveting joints - Wituschek, Simon; Kappe, Fabian; Meschut, Gerson; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In view of economic and ecological trends, the concepts for lightweight construction in transport systems are becoming increasingly important. These are frequently applied in the form of multi-material systems, which are characterized by the selective use of materials and geometries. One major challenge in the manufacturing of multi-material systems is the joining of the individual components to form a complete system. Mechanical joining processes such as semi-tubular self-piercing riveting are frequently used for this application but reach their limits concerning the number of combinations of geometry and material. In order to react to the requirements and to increase the versatility of semi-tubular self-pierce riveting, a process combination consisting of a tumbling process and a self-pierce riveting process has been presented previously. This process combination is used in this work to investigate the versatility and to identify the influencing parameters on it. For this purpose, experiments are conducted to identify process-side influence possibilities. The tests are performed with a dual-phase steel aluminum alloy to represent the varying mechanical characteristics of multi-material systems. Furthermore, the initial sheet thicknesses of the joining partners are varied in several steps. In addition to the geometric joint formation used to describe the undercut, the rivet head end position and the residual sheet thickness, the joining process, is also analyzed during the investigations. Further, the innovative joining process is evaluated by comparing it with a conventional self-piercing riveting process. The knowledge obtained represents a basis for the identification and evaluation of the versatility of the process combination.
Keywords: Mechanical Engineering; General Materials Science

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Identification of Requirements for FE Modeling of an Adaptive Joining Technology Employing Friction-Spun Joint Connectors (FSJC) - Oesterwinter, Annika; Wischer, Christian; Homberg, Werner (Metals)
The adaptive joining process employing friction-spun joint connectors (FSJC) is a promising method for the realization of adaptable joints and thus for lightweight construction. In addition to experimental investigations, numerical studies are indispensable tools for its development. Therefore, this paper includes an analysis of boundary conditions for the spatial discretization and mesh modeling techniques, the material modeling, the contact and friction modeling, and the thermal boundary conditions for the finite element (FE) modeling of this joining process. For these investigations, two FE models corresponding to the two process steps were set up and compared with the two related processes of friction stir welding and friction drilling. Regarding the spatial discretization, the Lagrangian approach is not sufficient to represent the deformation that occurs. The Johnson-Cook model is well suited as a material model. The modeling of the contact detection and friction are important research subjects. Coulomb’s law of friction is not adequate to account for the complex friction phenomena of the adaptive joining process. The thermal boundary conditions play a decisive role in heat generation and thus in the material flow of the process. It is advisable to use temperature-dependent parameters and to investigate in detail the influence of radiation in the entire process.
Keywords: General Materials Science; Metals and Alloys

Joining of multi-material structures using a versatile self-piercing riveting process - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Lechner, Michael; Meschut, Gerson (Production Engineering)
Due to the increasing use of multi-material constructions and the resulting material incompatibilities, mechanical joining technologies are gaining in importance. The reasons for this are the variety of joining possibilities as well as high load-bearing capacities. However, the currently rigid tooling systems cannot react to changing boundary conditions, such as changed sheet thicknesses or strength. For this reason, a large number of specialised joining processes have been developed to expand the range of applications. Using a versatile self-piercing riveting process, multi-material structures are joined in this paper. In this process, a modified tool actuator technology is combined with multi-range capable auxiliary joining parts. The multi-range capability of the rivets is achieved by forming the rivet head onto the respective thickness of the joining part combination without creating a tooling set-up effort. The joints are investigated both experimentally on the basis of joint formation and load-bearing capacity tests as well as by means of numerical simulation. It turned out that all the joints examined could be manufactured according to the defined standards. The load-bearing capacities of the joints are comparable to those of conventionally joined joints. In some cases the joint fails prematurely, which is why lower energy absorptions are obtained. However, the maximum forces achieved are higher than those of conventional joints. Especially in the case of high-strength materials arranged on the die side, the interlock formation is low. In addition, the use of die-sided sheets requires a large deformation of the rivet head protrusion, which leads to an increase in stress and, as a result, to damage if the rivet head. However, a negative influence on the joint load-bearing capacity could be excluded.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Provision of cross-domain knowledge in mechanical joining using ontologies - Zirngibl, Christoph; Kügler, Patricia; Popp, Julian; Bielak, Christian Roman; Bobbert, Mathias; Drummer, Dietmar; Meschut, Gerson; Wartzack, Sandro; Schleich, Benjamin (Production Engineering)
Since the application of mechanical joining methods, such as clinching or riveting, offers a robust solution for the generation of advanced multi-material connections, the use in the field of lightweight designs (e.g. automotive industry) is steadily increasing. Therefore, not only the design of an individual joint is required but also the dimensioning of the entire joining connection is crucial. However, in comparison to thermal joining techniques, such as spot welding, the evaluation of the joints’ resistance against defined requirements (e.g. types of load, minimal amount of load cycles) mainly relies on the consideration of expert knowledge, a few design principles and a small amount of experimental data. Since this generally implies the involvement of several domains, such as the material characterization or the part design, a tremendous amount of data and knowledge is separately generated for a certain dimensioning process. Nevertheless, the lack of formalization and standardization in representing the gained knowledge leads to a difficult and inconsistent reuse, sharing or searching of already existing information. Thus, this contribution presents a specific ontology for the provision of cross-domain knowledge about mechanical joining processes and highlights two potential use cases of this ontology in the design of clinched and pin joints.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Numerical Investigation of the Influence of a Movable Die Base on Joint Formation in Semi-tubular Self-piercing Riveting - Kappe, Fabian; Wituschek, Simon; de Pascalis, Vincenzo; Bobbert, Mathias; Lechner, Michael; Meschut, Gerson (Materials Design and Applications IV)
Due to economic and ecological requirements and the associated trend towards lightweight construction, mechanical joining technologies like self-piercing riveting are gaining in importance. In addition, the increase in lightweight multi-material joints has led to the development of many different mechanical joining technologies which can only be applied to join a small number of material combinations. This leads to low process efficiency, and in the case of self-piercing riveting, to a large number of required tool changes. Another approach focuses on reacting to changing boundary conditions as well as the creation of customised joints by using adaptive tools, versatile auxiliary joining parts or modified process kinematics. Therefore, this study investigates the influence of increased die-sided kinematics on joint formation in self-piercing riveting process. The aim is to achieve an improvement of the joint properties by superimposing the punch feed. Furthermore, it is intended to reduce required tool changes due to the improved joint design. The investigations were carried out by means of a 2D-axisymmetric numerical simulation model using the LS-Dyna simulation software. After the validation of the process model, the die was extended to include driven die elements. Using the model, different kinematics as well as their effects on the joint formation and the internal stress concentration could be analysed. In principle, the increased actuator technology enabled an increase of the interlock formation for both pure aluminium and multi-material joints consisting of steel and aluminium. However, the resulting process forces were higher during the process phases of punching and spreading.

Determining the influence of different process parameters on the versatile self-piercing riveting process using numerical methods - Kappe, Fabian; Zirngibl, Christoph; Schleich, Benjamin; Bobbert, Mathias; Wartzack, Sandro; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management

Increasing flexibility of self-piercing riveting by reducing tool–geometry combinations using cluster analysis in the application of multi-material design - Kappe, Fabian; Schadow, Luca; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers Part L Journal of Materials Design and Applications)

Determining the properties of multi‑range semi‑tubular self‑piercing riveted joints - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Meschut, Gerson (Production Engineering)

Approach to Determine the Characteristic Dimensions of Clinched Joints by Industrial X-ray Computed Tomography - Busch, Matthias; Köhler, Daniel; Hausotte, Tino; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (e-Journal of Nondestructive Testing)
Destructive micrograph analysis (MA) is the standard method for the assessment of clinched joints. However, during the joint preparation for the MA, geometric features of the joint can change due to elastic effects and closing cracks. X-ray computed tomography (CT) is a promising alternative to investigate the joint non-estructively. However, if the material properties of similar joining partners are the same, the CT is not able to correctly resolve surfaces in the joint that are close to or pressing onto each other. These surfaces are relevant for the determination of characteristic dimensions such as neck thickness and undercut. By placing a thin, highly radiopaque tin layer between the joining partners, the interfacial area in the reconstructed volume can be highlighted. In this work, a method for the localisation of the tin layer inside the joint as well as threshold value procedures for the outer joint contour in cross section images are investigated. The measured characteristic dimensions are compared with measured values from MA of the same samples and of samples without tin layer. In addition, possible effects of the tin layer on the joining point characteristics as well as problems of the MA are discussed.

Untersuchung zum Einfluss radioopaker Zwischenschichten bei der in-situ CT geclinchter Verbindungen - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (Tagungsband zur Werkstoffprüfung 2022)
Zur Qualitätssicherung von Clinchpunkten werden häufig ex-situ Methoden, wie etwa Schliffbildanalysen, eingesetzt. Diese ermöglichen jedoch nicht die Berücksichtigung von Phänomenen, die während der Belastung auftreten, da sich nach der Entlastung elastische Deformationen zurückbilden und Risse wieder schließen. Dagegen kann mit der in-situ Computertomographie (CT) der innere Deformationszustand des Clinchpunkts, z.B. während eines Scherzugversuchs, untersucht werden. Hierbei ist es für artgleiche Werkstoffe aufgrund der hohen Pressungen im Clinchpunkt schwierig, die Trennfläche zwischen den Fügepartnern im CT-Scan zu erkennen. Daher wird eine radioopake Zwischenschicht aus Zinn in die Trennfläche eingebracht. In dieser Arbeit wird der Einfluss der Zwischenschicht auf die in-situ CT-Scherzugprüfung untersucht. Hierzu werden sowohl Kraft-Verlängerungs-Kurven als auch die Geometrie der Clinchpunkte während der Belastung verglichen.

Clinching in In Situ CT—A Novel Validation Method for Mechanical Joining Processes - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (The Minerals, Metals & Materials Series)

Investigations on Combined In Situ CT and Acoustic Analysis during Clinching - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Key Engineering Materials)
Clinching is a cost efficient method for joining components in series production. To assure the clinch point’s quality, the force displacement curve during clinching or the bottom thickness are monitored. The most significant geometrical characteristics of the clinch point, neck thickness and undercut, are usually tested destructively by microsectioning. However, micrograph preparation goes ahead with a resetting of elastic deformations and crack-closing after unloading. To generate a comprehensive knowledge of the clinch point’s inner geometry under load, in-situ computed tomography (CT) and acoustic testing (TDA) can be combined. While the TDA is highly sensitive to the inner state of the clinch point, it could detect critical events like crack development during loading. If such events are indicated, the loading process is stopped and a stepped in-situ CT of the following crack and deformation development is performed. In this paper, the concept is applied to the process of clinching itself, providing a detailed three-dimensional insight in the development of the joining zone. A test set-up is used which allows a stepwise clinching of two aluminium sheets EN AW 6014. Furthermore, this set-up is positioned within a CT system. In order to minimize X-ray absorption, a beryllium cylinder is used within the set-up frame and clinching tools are made from Si3N4. The actuator and sensor necessary for the TDA are integrated in the set-up. In regular process steps, the clinching process is interrupted in order to perform a TDA and a CT scan. In order to enhance the visibility of the interface, a thin tin layer is positioned between the sheets prior clinching. It is shown, that the test-set up allows a monitoring of the dynamic behaviour of the specimen during clinching while the CT scans visualize the inner geometry and material flow non-destructively.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science